Surgical Treatment for Esophageal Leiomyoma: 13 Years of Experience in a High-Volume Tertiary Hospital - A-Lai, Gu-Ha; Hu, Jian-Rong; Yao, Peng; Lin, Yi-Dan (Frontiers in Oncology, 2022)
Background Esophageal leiomyoma is the most common benign tumor in the esophagus. Thoracotomy and thoracoscopy are both elective for esophageal leiomyoma enucleation. This study aimed to present surgical experience in our center and explore more suitable surgical methods for different situations. Methods We conducted this retrospective study by collecting data from patients who underwent esophageal leiomyoma enucleation through thoracotomy or thoracoscopy from January 2009 to November 2021 at West China Hospital Sichuan University. Results A total of 34 patients were enrolled for analysis. All patients were diagnosed with a single esophageal leiomyoma. There were 25 men and 9 women. The mean age was 44.41 years (range, 18-72 years), the mean longest diameter was 4.99 cm (range, 1.4-10 cm), the esophagus was thoroughly circled with leiomyoma in 10 patients, 10 patients underwent thoracotomy to enucleate leiomyoma, while others underwent thoracoscopic enucleation. No perioperative deaths occurred. Between the thoracotomy group and thoracoscopy group, baseline characteristics were comparable except for gastric tube status (P=0.034). Patients were inclined to undergo the left lateral surgery approach (P=0.001) and suffered esophagus completely encircled by leiomyoma (P=0.002). Multivariable logistic regression analysis demonstrated that the left lateral surgery approach (P=0.014) and esophagus completely encircled by leiomyoma (P=0.042) were risk factors for thoracotomy of leiomyoma enucleation, while a larger tumor size demonstrated no risk. The median follow-up time was 63.5 months, and no deaths or recurrence occurred during the follow-up period. Conclusion Thoracotomy enucleation of the leiomyoma was recommended when the esophagus was thoroughly encircled by the leiomyoma and the left lateral surgery approach was needed. However, tumor size demonstrated less value for selecting a surgical approach.